Effect of phytase supplementation on apparent phosphorus digestibility and phosphorus output in broiler chicks fed low-phosphorus diets (International Journal of Health, Animal Science and Food Safety, 2015)
This study was conducted to evaluate the effect of supplemental phytase in broiler chicks fed different low levels of total phosphorus (P) on the apparent phosphorus digestibility (APD) and phosphorus output (PO) in the faeces and ileal digesta. After fed a standard broiler starter diet from day 0 to 14 post-hatch, a total of 144 male broiler chicks were allocated to 6 groups for a 7-d experiment with a 2 × 3 factorial design comparing phytase (supplemented without (CTR) or with 400 FTU/kg phytase (PHY)) and total P levels (2.0, 2.5 and 3.0 g/kg). The faecal samples were collected from day 17 to 21 post-hatch. At 22 days of age, all the chicks were slaughtered and collected the ileal digesta. Phytase supplementation significantly (P < 0.01) increased APD and decreased PO in the faeces and ileal digesta in comparison with the CTR group. In addition, PO in the faeces expressed as g/kg DM diets and faeces (Diet × P level, P = 0.047 and < 0.01, respectively) as well as PO in the ileal digesta expressed as g/kg DM digesta (Diet × P level, P = 0.04) were affected by diet and P level, which were due to the significant reduction (P < 0.01) by PHY supplementation to the diets with 3.0 g/kg total P. The results evidenced that supplemental phytase improved the APD and PO when chicks was fed 3.0 g/kg total P diet, while lower total P levels may limit exogenous phytase efficacy.
Keywords: Apparent phosphorus digestibility; Chicks; Low-phosphorus; Phosphorus output; Phytase